Competence-based Learning: A proposal for teachers’ self– assessment - Martínez Martínez, Aurora; Cegarra Navarro, Juan Gabriel; Rubio Sánchez, Juan Antonio (Profesorado, Revista de Currículum y Formación del Profesorado, 2012)
The addition of Spanish universities to the European Higher Education Area (EEES) carry various and profound changes. Among these important changes is the firm commitment to focus the attention of educational processes in student learning and, more specifically, learning outcomes, which are measured through competences.This article discusses the need to change the evaluation processes. To this end, we started the conceptualization of competences, also discusses the implications of the teaching competences and determine the features that should have a competences assessment. In this paper when we talk about skills assessment we will refer, first, the student’s learning competences and the other to the instructor’s teaching competences.